Three-dimensional flight trajectories in three European butterfly species. - Rauscher, Luca Marie (Jihočeská univerzita, 2023)
The flight path of three chosen European butterflies were studied. The trajectories were reconstructed, disentangled into flight path characteristics and subsequently statistically analyzed.
Three-dimensional flight trajectories in three European butterfly species.
-
Keywords: Butterflies; 3D-trajectories; flight parameters; flight paths; flight performances; comparative Analysis.; Butterflies; 3D-trajectories; flight parameters; flight paths; flight performances; comparative Analysis.